Movement prototypes in the performance of the handspring on vault - Mack, M.; Hennig, L.; Heinen, T. (Science of Gymnastics Journal, 2018)
Most research concerning the kinematic analysis of gymnastics skills only deals with selected variables, thereby often ignoring the holistic nature of the analyzed skills. Therefore, the goal of this study was to develop an innovative approach to analyze the front handspring on vault. To gain comprehensive insight into the aforementioned motor skill, different skill prototypes should be detected and their variant and invariant characteristics should be investigated. The digitized video sequences of 60 handspring trials from ten female gymnasts were used for kinematic analysis. Time courses of six joints were analyzed by means of a hierarchical cluster analysis. In addition, the coefficients of variation were calculated. Results revealed that four distinct prototypical movement patterns could be identified for the handspring on vault in female near-expert gymnasts. The movement patterns within each prototype are thereby more similar to each other than the movement patterns between the four prototypes. The four different prototypes can be distinguished by certain variant and invariant characteristics, that become obvious when inspecting the time courses of the hip and shoulder angles, as well as the time course of the coefficient of variation. In light of the training process in gymnastics, the study provides further evidence for strongly considering gymnasts` individual movement patterns when it comes to motor skill acquisition and optimization.